EXPLORING BARRIER FACTORS PUBLICATION OF RESEARCH ARTICLES IN REPUTABLE INTERNATIONAL JOURNALS - AGUS PURWANTO (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
This study aims to explore  the inhibiting factors for internal lecturer productivity publication of scientific papers in indexed international journals,  lecturers' expectations of campus managers to increase the productivity of the publication of scientific papers in indexed international journals. This research is a survey research conducted at the Postgraduate Program at a private university in Banten. with respondents totaling 120 lectures . The data collection technique used a questionnaire. Data analysis technique using descriptive statistical analysis techniques. The results of the study are described as follows. Factors The obstacle to the publication of scientific papers in indexed international journals comes from external factors, namely busy work, the amount of costs, limited subscriptions to print journals, limited subscriptions to online journals, and limited access to printed journals. Lecturers hope to increase publication productivity scientific papers in indexed international journals, namely improvements and enhancements in socialization, accessinformation and services, writing and English language training, free translation assistance, establish cooperation with various parties, as well as subscriptions to online and print journals.